مقارنة ثخانة طبقة الألياف العصبية الشبكية (RNFL) وموجودات الساحة البصرية عند المرضى الزرقيين - يوسف, حبيب (Latakia University Journal -Medical Sciences Series, 2018)
الهدف: تحديد ثخانة طبقة الألياف العصبية الشبكيةRNFL التي تصبح عندها أذية الساحة البصرية VFقابلة للكشف الطرائق: شملت الدراسة 29 شخص طبيعي و 36 شخصاً زرقياً (عين واحدة لكل شخص), خضع جميع المرضى لفحص الساحة البصرية بجهاز OCTOPUS برنامج الزرق 2-30 وقياس ثخانة طبقة الألياف العصبية حول الحليمة باستخدام جهاز HIEDELBERG-SPECTRALIS SD_OCT النتائج: أظهرت مقارنة نتائج الاختبارين حساسية أعلى للOCT مقارنة بالساحة البصرية. وكانت ثخانة RNFL الوسطية التي ظهر عندها أذية VF 87 ميكرون. وكانت قيمة ثخانة RNFL العلوية التي ترافقت مع أذية ساحة بصرية سفلية حوالي 101 ميكرون. في حين كانت ثخانة RNFL السفلية التي ترافقت مع أذية ساحة بصرية علوية 75 ميكرون, وكان الفرق بين قيم RNFL في حالتي الساحة البصرية والساحة الزرقية هاماً إحصائياً (p<0.001). الخلاصة: في الزرق مفتوح الزاوية, يبدو أنه من الضروري حصول ترقق هام في طبقة RNFL قبل أن تصبح عيوب الساحة البصرية قابلة للكشف. Aim: to determine the value of RNFL thickness at which visual field defect becomes detectable. Methods: Our study included 29 normal subject and 36 glaucomatous patient (one eye per person) .Every person was examined by OCTOPUS perimetry with glaucoma 30-2 program, and peripapillary RNFL thickness was measured by HIEDELBERG-SPECTRALIS SD_OCT. Results: comparison of results showed higher sensitivity of OCT compared to Perimetry. Mean RNFL thickness at which visual field defect showed was 87 microns. Superior RNFL thickness value which correlated with inferior visual field defect was 101 microns, whereas inferior RNFL thickness value which correlated with superior visual field defect was 75 microns .and the difference in RNFL thickness between normal and glaucomatous visual field was significant (p<0.001). Conclusion: in open-angle glaucoma , it needs significant thinning in RNFL before visual field defects becomes detectable.